Comparing Problem-Based Learning (PBL) and Active Learning in Augmenting Students’ Proficiency in Reading Comprehension - Indriyani, Vivi; Fendi, Hasri; Jasmienti, Jasmienti; Rahmayani, Rizka Dwi (FKIP Universitas Lampung, 2024)
Abstract: Comparing Problem-Based Learning (PBL) and Active Learning in Augmenting Students' Proficiency in Reading Comprehension. Objective: To compare the influence of the PBL Model and the Active Learning Model on students' understanding of BIPA learning method material. Method: This research uses experimental methods and a quasi-experimental research design. A two group pretest-posttest research design was used for this study. Using purposive sampling technique, the sample for this investigation was selected from two classes. This research's data collection approach requires administering tests. SPSS is a software application used for statistical data analysis. Active Learning and PBL influence students' reading comprehension of lesson material, according to the findings of this research. Findings: Based on testing the two models, the results showed that the average learning outcomes of students who used the Active Learning model could not be differentiated from those of students who used the PBL model. Conclusion: The results of the SPSS analysis of the N-gain Score show that both the PBL and Active Learning models are very effective in improving students' reading comprehension of the subject matter. Keywords: problem based learning, active learning, reading comprehension.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202406